2012
DOI: 10.1016/j.bbamcr.2011.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a nuclear carbonic anhydrase in Caenorhabditis elegans

Abstract: Background Carbonic anhydrases (CA) catalyze the inter-conversion of CO2 with HCO3 and H+, and are involved in a wide variety of physiologic processes such as anion transport, pH regulation, and water balance. In mammals there are sixteen members of the classical α-type CA family, while the simple genetic model organism C. elegans codes for six αCA isoforms (cah-1 through cah-6). Methods Fluorescent reporter constructs were used to analyze gene promoter usage, splice variation, and protein localization in tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…The six alpha-carbonic anhydrase isoforms 1 to 6 are encoded for in the Caenorhabditis elegans genome (cah-1, cah-2, cah-3, cah-4, cah-5 and cah-6) [44]. Wormbase searches revealed that the murine ( Mus musculus) CAII gene has similar homology to the C.elegans gene cah-3.…”
Section: Resultsmentioning
confidence: 99%
“…The six alpha-carbonic anhydrase isoforms 1 to 6 are encoded for in the Caenorhabditis elegans genome (cah-1, cah-2, cah-3, cah-4, cah-5 and cah-6) [44]. Wormbase searches revealed that the murine ( Mus musculus) CAII gene has similar homology to the C.elegans gene cah-3.…”
Section: Resultsmentioning
confidence: 99%
“…Out of six predicted α-CAs in C. elegans, three lack residues important for catalysis. Only CAH-3 and CAH-4 are active in heterologous CA activity assays (Sherman et al 2012). Based on its published expression pattern, cah-4 seems to be absent from BAG (Bretscher et al 2011), and here we show that cah-3 is also repressed in these cells.…”
Section: Sequences In Thementioning
confidence: 76%
“…Interestingly, in response to metabolic stress nucleocytoplasmic malate dehydrogenase (MDH) has been reported to regulate p53 transcriptional activity . In a recent study, carbonic anhydrase has also been shown to reside in the nucleus in Caenorhabditis elegans and suggested to play a role in oxidative stress resistance .…”
Section: Resultsmentioning
confidence: 99%